DESIGN RESEARCH: LINTASAN PEMBELAJARAN STATISTIKA UNTUK MENUMBUHKAN KEMAMPUAN LITERASI STATISTIK SISWA - Lukman Fakhmi; Pinta Deniyanti Sampoerno; Meiliasari Meiliasari (STKIP Andi Matappa, 2021)
Statistical literacy is one of the abilities that society expects as a result of education in schools. The purpose of this study is to develop a learning trajectory on statistical material using the Indonesian Realistic Mathematics Education (PMRI) approach to foster students' statistical literacy skills. The solution offered in this study is to use the help of data presentations in the form of dot plots and the context of Body Mass Index (BMI). This research was conducted in SMPN 10 Palembang with heterogeneous abilities. This study used design research methods by performing three phases like preparation and design, teaching experiments, and retrospective analysis. Data collection techniques used students’ written work, interviews, and video recording. The instruments of this study used a hypothetical learning trajectory, students’ activity sheets, worksheets, observation sheets, interview sheets, and evaluation tests. Retrospective analysis results show that the implementation of PMRI using dot plots and BMI context can foster students’ statistical literacy ability.